Accidental colchicine overdose. A case report and literature review. Issue 3 (1st May 2002) - Maxwell, M J; Muthu, P; Pritty, P E
Abstract : Colchicine overdose is uncommon but potentially life threatening. It is a safe drug when used according to established therapeutic guidelines but causes serious systemic effects if ingested in doses that exceed the recommendations. Overdose must therefore be recognised early and treated appropriately to optimise the outcome. A fatal case of colchicine overdose caused by inappropriate self medication is reported and to the best of the authors' knowledge, there has been no report of fatal accidental overdose in the United Kingdom. The pharmacology of colchicine, the clinical features associated with overdose, and the options for treatment are discussed.